Redox and melting characteristics of Mn-based ores for high-temperature thermochemical energy storage - Liu, Lei; Xu, Wenting; Liu, Hanzi (Frontiers in Energy Research, 2024)
Redox and melting characteristics of Mn-based ores were investigated in order to test their potential use in thermochemical energy storage (TCES). Two Mn-based material (FJ and LY) were natural ores with Mn content higher than 35 wt%, and one Mn-based material was prepared by adding MgO-kaolin inert support into LY ores in order to increase its melting temperature. Cyclic reduction and oxidation reactivity of these Mn-based material were studied in thermogravimetric analysis (TGA), and melting behaviors of these materials were investigated in a melting test setup with an optical camera-image system. It was found that the oxygen capacity of FJ Mn ore can approach ~1.50 wt%, while there was only 0.42 wt%~0.69 wt % oxygen capacity for LY Mn ore. The deformation temperature of FJ Mn ore is higher than that of LY Mn ore, and the melting temperatures of LY Mn ore can be improved a lot with the adding of MgO-kaolin inert support, while the reactivity is decreased due to the adding of MgO-kaolin inert material. This study proves that the manganese ores with high oxygen capacity and deformation temperature have potential as TCES materials. For some manganese ores with low deformation temperature, it is necessary to improve their melting temperatures and ensure oxygen capacity for high-temperature TCES applications.